Investigating the Nanocomposite Thin Films of Hematite α-Fe2O3 and Nafion for Cholesterol Biosensing Applications - Sulania, Indra; Pricilla, R. Blessy; Lakshmi, G. B. V. S. (Frontiers in Nanotechnology, 2020)
Nanocomposite materials are multiphase solid materials which have two or more component materials, with different physical and chemical properties, blended together to form a newer material with unique properties which make them good candidates for numerous applications. In this study, we have fabricated thin films of nafion (polymer) and α-Fe2O3 (nanoparticles) nanocomposite on indium tin oxide (ITO) coated glass substrates, as it showed an enhanced ionic conductivity for cholesterol biosensor application. SEM and AFM revealed the formation of nanorod structured α-Fe2O3 in the films. The cyclic voltammetry (CV) studies of nafion--Fe2O3/ITO revealed the redox properties of the nanocomposites. The sensing studies were performed on nafion+-Fe2O3/CHOx/ITO bioelectrode using differential pulse voltammetry (DPV) at various concentrations of cholesterol. The enzyme immobilization leaded to the selective detection of cholesterol with a sensitivity of 64.93×10-2 A (mg/dl)-1 cm-2.